The temporal structure between retrieval and anticipation in (The Treatise of Dependencies and Tornadoes) - مصطفى, اسماعيل ابراهيم; مدحت, رۆژان أنور (Sulaimani Journal for Humanities, 2019)
This is a part of a PhD thesis that attempts to monitor the two techniques of time in narrating, the story at any time when the narrator narrates his story. Due to the importance of his time organization we try to follow the approach of (Gerard Genet) here, and since the story occupies a place in Arabic literature and the story contain poetry and prose and criticism and imagination as a harmonious combination, the student can apply the new curriculum and require new meanings in it.